Bery Engebretsen letter to Thomas H. Kent regarding bird sightings, December 2, 1995 - Engebretsen, Beryet al (1995)
Field notes contributed by Bery Engebretsen in a letter to Thomas H. Kent. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1995. Epson - sheet feed